Cloning and Co-Expression of Lipase and its Specific Foldase from Ralstonia pickettii BK6 - Muhamad Azwar Syah; Andreas Adhi Satya; Esti Puspitasari; Antonius Suwanto; Nisa Rachmania Mubarik (HAYATI Journal of Biosciences, 2023)
This study aimed to obtain a functional lipase (LipRM) from Ralstonia pickettii BK6 through a co-expression involving its foldase. The ORF of the LipRM was 999 bp while the gene encoding of lipase-specific foldase (LifRM) was 1,030 bp. LipRM and LifRM genes were cloned into a plasmid and were successfully co-expressed in Escherichia coli strains to produce functional LipRM. Enzyme activity from partially purified enzymes showed quite surprising results, LipRM activity in E. coli BL21 (DE3) was 25.84 U/ml, while the other strains (DH5α, HB101, S17-1λpir) were 628.98 U/ml, 761 U/ml, and 1206.46 U/ml, respectively. The highest relative activity of LipRM was found at 50-55°C and pH 7-8 with pNP-laurate (C12) as the preferred substrate specificity. LipRM activity was enhanced sharply in the presence of 30% organic solvents (methanol and ethanol) but decreased by more than 50% in the presence of detergents. This study was the first to report heterologous expression of Ralstonia pickettii lipase employing its native foldase resulting in functional lipase from subfamily I.2.